Fetal Brain Pathology: A Comparison of MR Imaging and Ultrasound Screening - Athanasiadis, Apostolos; Polichronou, P.; Zavlanos, A.; Gerede, A.; Asimakopoulos, E.; Bontis, J. (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVES: To compare prenatal MR imaging and ultrasound screening for the diagnosis of fetal brain pathology. STUDY DESIGN: Retrospective multicenter study of 62 fetuses diagnosed with brain pathology at 2nd trimester ultrasound scan during the period 2003-2008. In these fetuses prenatal MR imaging was performed. RESULTS: In 38 of 53 (71.7%) cases the ultrasound diagnosis was isolated ventriculomegaly (Group A), while in the rest 15 of 53 (28.3%) cases other brain abnormalities were diagnosed (Group B). Ultrasound scan and MR imaging findings were similar in 35 of 38 (97.2%) fetuses from Group A and in 11 of 15 (73.3%) from Group B. In a total 46 of 53 (86.8%) cases, no significant discrepancy between US and MR imaging findings was observed. CONCLUSION: MRI providing ascertainment or a differential diagnosis of an abnormal US finding in brain pathology. However, in most of the cases, it seems that MR imaging does not provide additional information concerning fetal brain pathology than ultrasound scan alone.